Utilization of Information and Communication Technology in Coordination Between the National Library with the Provincial Library - Gammayani, Dimas A.; Nabawi, Irham Hanif; Alfatih, Muhammad Irsyad (Universitas Airlangga, 2015)
Changes are rapidly occur in this world, especially developments in the field of information and communication technology. Man must be able to adjust quickly to keep up. Developments in information and communication technology has made it easier for people in work. Utilization of information and communication technology are expected to make work performed by humans is more effective and efficient. National Library of Indonesia mandated by Law No. 43 of 2007 as an adviser to all types of libraries throughout Indonesia. In carrying out the task, the National Library should coordinate with local government including the provincial government, represented by the provincial library which can be said to represent the provincial government in the affairs of the library. National Library of Indonesia in coordination with the provincial library has been facilitated by information and communication technology such as telephone, fax and internet. In addition, coordination can also be done through conventional correspondency or direct face to face. This study tried to define which communication system that is commonly used by the National Library of Indonesia when coordinating with the provincial library and the reasons that lie behind them. The method used in this research is descriptive with a participatory approach, the researchers and respondents are equal and shared a mutual cooperation. This research indicates that face-to-face coordination is more preferred, because face-to-face coordination offers a social and economical benefit.